Attitudes and behaviours associated with HIV transmission in men who have sex with men in Portugal – a qualitative study - Filipa Correia; Kenneth Camargo; Paulo Nossa; Ana Aboim Horta; Margarida Correia-Neves; Alice Delerue-Matos (Global Public Health)
HIV pandemic continues to affect key populations more than the general population, namely young men who have sex with men (MSM) [UNAIDS. (2023). The path that ends AIDS: UNAIDS global AIDS update 2023. Joint United Nations Programme on HIV/AIDS. https://www.unaids.org/sites/default/files/media_asset/2023-unaids-global-aids-update_en.pdf]. This study aimed to identify and better understand the attitudes and behaviours associated with HIV transmission in young MSM, and their awareness and motivation to use pre-exposure prophylaxis (PrEP). In 2022 and 2023, we interviewed 23 MSM between 20 and 30 years old. A hybrid methodology – inductive and deductive – was used for content analysis. Trust in partners, drug use, fetishisation regarding condomless sex and yielding to a partner's desire due to lack of assertiveness were highlighted as motivations for unprotected sex. Shame and fear of stigma were identified as potential inhibitory factors for HIV testing. Some concerns and lack of awareness regarding PrEP were noted, along with barriers to access, due to long waiting times for consultations and lack of knowledge or judgment by healthcare professionals. This study reinforces the need to invest in sex education and empowerment strategies, through a sexual orientation-sensitive approach, in the context of health education and care provision, as well as the need for training and streamlining PrEP fast-track protocols.